TLR4 and prostaglandin pathways at the crossroads of endotoxemia-induced lipolysis - Chirivi, Miguel; Abou-Rjeileh, Ursula; Myers, Madison; Parales-Giron, Jair; Worden, Lynn; Lock, Adam L.; Contreras, G. Andres (Frontiers in Immunology, 2025)
BackgroundDuring endotoxemia, immune activation rapidly increases energy needs. To meet these demands, white adipose tissue (WAT) mobilizes fatty acids through lipolysis. While fatty acids serve as energy-dense substrates, they also act as precursors for lipid mediators, including prostaglandins (PGs), that drive inflammation. The dual role of WAT is crucial during endotoxemia, wherein both energy needs and inflammatory signals are amplified. However, the mechanisms by which WAT regulates lipolysis during endotoxemia are not well understood. Dairy cows serve as an excellent model for studying endotoxemia due to the high incidence of the condition and increased susceptibility to lipolysis dysregulation observed during the periparturient period.MethodsOur study aimed to define the effects of endotoxemia on lipid mobilization and the regulatory role of PG receptors on the activity of key lipases within WAT. We used an in vivo lipopolysaccharide (LPS) infusion model of endotoxemia in lactating dairy cows (n = 4) to evaluate WAT inflammation, lipase activity, and PG receptor abundance 24 hours post-infusion. Additionally, we employed in vitro models using bovine adipocyte progenitor cells and mature adipocytes (n = 6) to investigate the effects of LPS exposure on lipid accumulation, lipolysis, arachidonic acid release, cyclooxygenase-2 (COX-2) activity, and EP receptor expression. ResultsIn lactating dairy cows, we observed enhanced WAT inflammation, reduced lipolysis, and decreased activity of adipose triglyceride lipase (ATGL) and hormone-sensitive lipase (HSL) 24 hours post-infusion. Notably, endotoxemia reduced the abundance of PG receptors EP2 and EP4 in WAT. Using the in vitro model, we found that adipocyte progenitor cells exposed to LPS during differentiation exhibited increased lipid accumulation after four days of adipogenic induction. In contrast, in mature adipocytes, LPS exposure (7 h) intensified lipolysis, an effect that was attenuated when toll-like receptor 4 (TLR4) was silenced. LPS also enhanced the release of arachidonic acid and adipocytes’ cyclooxygenase-2 (COX-2) activity, leading to increased biosynthesis of prostaglandin E2 (PGE2). LPS also increased the expression of EP2, a PGE2 receptor, while simultaneously reducing EP4 content. PGE2 activated lipolysis in an EP4 receptor-dependent manner. COX inhibition reduced the biosynthesis of PGE2, inhibited lipolysis, and upregulated EP4 expression. ConclusionThese data demonstrate that, during endotoxemia, TLR4 activation in bovine adipocytes triggers lipolysis via prostaglandin E2-dependent mechanisms. In addition, LPS modulates EP receptor expression, resulting in alterations in lipid mobilization. Together, these data provide initial evidence of prostaglandin receptors as possible targets for modulating WAT lipid trafficking during endotoxemia.